2020
DOI: 10.3389/fimmu.2020.00104
|View full text |Cite
|
Sign up to set email alerts
|

The Imbalance of Circulating Follicular Helper T Cells and Follicular Regulatory T Cells Is Associated With Disease Activity in Patients With Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disease affecting the colon and rectum, in which the abnormality of B cells is involved in both its pathogenesis and progression. Follicular helper T cells (TFH) play an important role in assisting the immune function of human B cells in germinal centers, and follicular regulatory T cells (TFR) have the function of inhibiting TFH and germinal center B cell responses. The significance of circulating TFH and TFR in ulcerative colitis (UC) remains unclear. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…TFH cells may be defined as CXCR5+ CD4+ cells yielding TFH cell frequencies around 20% in peripheral blood ( Figure 1 C ). 33 TFH cell frequencies are considerably lower if more specific markers such as PD-1 or ICOS are used (2%–10%) 26 and are well in the range of the frequencies we describe here when CXCR5+ PD-1 high cells are analyzed. 34 Importantly, this subset most closely resembles lymphatic tissue–derived TFH cells.…”
Section: Discussionsupporting
confidence: 67%
“…TFH cells may be defined as CXCR5+ CD4+ cells yielding TFH cell frequencies around 20% in peripheral blood ( Figure 1 C ). 33 TFH cell frequencies are considerably lower if more specific markers such as PD-1 or ICOS are used (2%–10%) 26 and are well in the range of the frequencies we describe here when CXCR5+ PD-1 high cells are analyzed. 34 Importantly, this subset most closely resembles lymphatic tissue–derived TFH cells.…”
Section: Discussionsupporting
confidence: 67%
“…We previously reported that active UC patients possessed higher levels of Tfh cells and CXCR3 − CCR6 − Tfh2 subsets but decreased Tfr cells in peripheral blood [9]. In order to further our research, we studied the expression of ICOS and PD-1 on Tfh cells.…”
Section: Circulating Icos + Pd-1 + and Icos + Pd-1 + Tfh Cells Werementioning
confidence: 99%
“…Tfh cells are crucial for the differentiation and development of B cells, and abnormality of effective B cells was confirmed to be involved in the pathogenesis of UC [9][10][11][12][13]. To further study the clinical significance of circulating ICOS + , PD-1 + and ICOS + PD-1 + Tfh cells in the pathogenesis of UC, we analyzed their associations with functional B cell subsets.…”
Section: Activated Icos + Pd-1 + Tfh Cells Were Related To B Cell Funmentioning
confidence: 99%
See 2 more Smart Citations